Respuesta :

Answer:

(2).

Step-by-step explanation:

We have the expression:

[tex]\displaystye{\ln(\displaystyle{\frac{\sqrt{e}}{y^3})}[/tex]

First, we can use the difference property of logarithms:

[tex]\ln(x/y)=\ln(x)-\ln(y)[/tex]

Hence, this is equivalent to:

[tex]=\ln(\sqrt{e})-\ln(y^3)[/tex]

We can rewrite the left as:

[tex]=\ln(e^\frac{1}{2})-\ln(y^3)[/tex]

Now, we can use the power property:

[tex]\ln(a^b)=b\ln(a)[/tex]

Essentially, we move the exponent to the front.

Hence, this yields:

[tex]=\frac{1}{2}\ln(e)-3\ln(y)[/tex]

The natural log of e is simply 1. Hence:

[tex]=\frac{1}{2}-3\ln(y)[/tex]

Combine fractions:

[tex]\displaystyle{=\frac{1}{2}-\frac{6\ln(y)}{2} \\ =\frac{1-6\ln(y)}{2}}[/tex]

Hence, our answer is (2).

ACCESS MORE